Discussion - Of Messrs. Gibb and Philp's Paper on The Constitution of Mattes Produced in Copper-Smelting (see Trans., xxxvi., 665) (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1908)
Allan Gibb, Queensland, Australia (communication to the Secretary*):—It is gratifying that Mr. Edward Keller,' who has clone so much work elucidating the principles of copper-metnllurgy, should have subjected only that portion of our investigation relating to magnetic iron oxide to anything like adverse criticism. Situated as we were on a rnining-camp, it was impossible to undertake work that would cover all the intricate possibilities connected with the materials commonly classed as matte. We therefore began the investigation on matte produced from ores that contained no other components than the sulphides of copper and iron that would be likely to enter into the composition of matte. We were, accordingly, free from ally possibility of magnetic iron oxide entering the matte, unless it were formed in the operation itself. The work done on this subject was incomplete, and the results thereof recorded as giving only negative evidence as to the absence of magnetic iron oxide. It would have been better to have left the matter open, as " not proven." The trend of the investigation was to account for the insufficiency of sulphur in matte to satisfy the requirements of ferrous and cuprous sulphides. So far as our deductions are correct, it was unnecessary to consider the (in our samples) somewhat doubtful constituent, magnetic iron oxide. The mattes that mere investigated were among those mentioned by Mr. Keller, " which scarcely show ally magnetic property." The samples showed no such property. There was no unaccountable variation in the specific gravity, which only varied, as would be expected, with the proportion of ferrous sulphide. I have had experience in smelting ores of which the gangue was a siliceous magnetite, both in blast- and rever-beratory furuace. The mattes so produced contained magnetic